Begging in Geneva: Which Right to the City? - Colombo, Annamaria; Reynaud, Caroline; de Coulon, Giada (Environnement urbain, 2016)
Based on a study that we carried out in Geneva between 2013 and 2015, this paper suggests that the anti-begging law adopted by the Geneva High Council in 2007 can be understood a way of managing urban cohabitation with marginalized populations. In response to this “poverty management”, we argue that the continued occupation of the public space by the people wh o practice begging can be understood as them implementing their own “right to the city” anyway, in the subversive sense meant by Lefebvre.